The Influence of Leadership on Performance with Work Life Balance as an Intervening Variable at BPJS Employment Sumbagut Regional Office - Sitinjak, Aristoteles; Isa Indrawan, Muhammad (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research was conducted to determine the influence of leadership on performance with work life balance as an intervening variable at the BPJS Employment Regional Office of Sumbagut, this type of research uses quantitative, the data source for this research uses primary data, this research was conducted at the BPJS Employment Regional Office of Sumbagut, the population of this research is 130 employees using a sampling technique, namely Slovin, so the sample used is 97 employees. Collecting respondent data using and distributing questionnaires. The research method used is expert analysis and the measuring tool uses Smart PLS version 3. The results of this research are as follows: Leadership has a positive and insignificant effect on performance with an original sample value of 0.068 and a P value of 0.477. Leadership has a positive and significant effect on Work Life Balance with an original sample value of 0.686 and a P value of 0.000. Work Life Balance has a positive and significant effect on performance with an original sample value of 0.812 and a P value of 0.000. Work Life Balance is able to become an intervening variable and influence the Leadership variable on Performance indirectly with an original sample value of 0.557 and a P value of 0.000.